(untitled) (Damascus University Journal of agriculture sciences, 2022)
The current research was performed to study the effects of growing oyster mushrooms (Pleurotus ostreatus) in improving the nutritional value of the substrates of the mushroom. During the estimation of the coefficients of digestion of their nutrients in the diets provided to rabbits. Wheat straw was used as a base for growing medium as first group (A), olive pruning leftover as second group (B), a mixture of wheat straw and tomato thrones at ratio of 50% of each, respectively as third group (C), and in the fourth group the wheat straw and cotton cup at a ratio of 80% and 20%, respectively. Chemical analysis was performed on the substrates, where dry matter, crude protein, crude fat, ash and crude fiber were determined in the substrates mentioned above, then these substrates were introduced into ration blends at 20%, and used in feeding eight groups of male rabbits (6 month old) and nearly 2 kg weight (3 rabbits, each group) for determine coefficient of digestibility of rations. The results of digestibility coefficient experiment revealed an increment in the coefficient of digestibility of dry matter in all rations which contain the substrates after mushroom growing, where it increased from 60.24, 58.34, 61.64 and 61.16%, respectively before growing into 62.92, 60.63, 62.54 and 62.01%, respectively after growing, at significant differences for each of groups A, B and C. The digestibility coefficient of protein was also improved from 76.86, 68.39, 74.87 and 78.70% into 82.44, 75.70, 79.33 and 78.34%, respectively, at significant differences for all groups except for group D, and in pertain to crud fibers, the digestibility coefficient increased for all rations which contained the substrates after mushroom growing in comparison of they before growing with significant differences (P>0.05), where the percent of fibers was increased in substrate A at 55.43% and in substrate B at 10.55% and at 16.74 and 34.21% in the substrates C and D, respectively. These results lead to the importance of developing oyster mushrooms on coarse plant wastes in improving the digestibility of dry matter, protein and fiber in them, which leads to improvement in their nutritional value in animal nutrition